INTEGRATING SOCIAL-EMOTIONAL LEARNING IN FOREIGN LANGUAGE CLASSROOMS: BENEFITS AND STRATEGIES (Scientific journal of the Fergana State University, 2026)
Social-Emotional Learning (SEL) — the development of self-awareness, self-management, social awareness, relationship skills, and responsible decision-making — is increasingly recognized as central to effective education. When applied to foreign-language teaching with young learners, SEL supports motivation, reduces language anxiety, strengthens classroom community, and provides the emotional vocabulary students need to use the target language meaningfully. This article synthesizes theory and empirical findings, outlines practical classroom strategies, discusses assessment and teacher preparation issues, and suggests directions for future research.